Técnicas de processamento digital de imagens para análise de integridade do dossel - um modelo em mata semidecídua - Yamada, Thiago (Universidade Federal de São Carlos, 2014)
The forests management and conservation are recently subjects discussed throughout the world, because they are directly correlation with the maintenance of environmental functions and services provided by natural environments. With growth of urban centers and extensive agriculture the natural areas have suffered and are suffering a big pressure making arise degraded areas constantly that encourage the recuperation movement in those areas. Moreover, the selective cut and the formation natural or artificial clearings make discontinuities in the canopy, irregularities reflected in the structure and profile. However, to realize the restoration and management, for example, a forest, first must to know your conservation state. This thesis intend to map more and less conserved areas through the analysis of structure and integrity in the canopy, realized with: canopy cover images, canopy closure images, vertical profile sketch, panchromatic image HRC of satellite CBERS-2B, and techniques digital image processing, beyond field survey. With intention to create a model able to identify, map, and monitor the forest degraded.
Keywords: Ecologia das florestas; Cobertura do dossel; Integridade do dossel; Processamento de imagens - técnicas digitais; Fragmento de floresta estacional semidecídua; Mata semidecídua; Imagens da cobertura do dossel; Digital image processing; Semideciduous forest fragment; Canopy cover; Canopy integrity; Forest ecology; CIENCIAS BIOLOGICAS::ECOLOGIA